Exploring the Influence of Human Resource Management Strategies on Employee Retention: A Detailed Empirical Analysis in Private Higher Education Institutions - Chi, Wong Rui; Vasudevan, Asokan; Wang, Annie; Ramachandran, Sharmila; Balakrishnan, Rajani; Galdolage, Badra Sandamali; Maniam, Vikineswaran A (Journal of Ecohumanism, 2024)
This study explores the influence of human resource management strategies on employee retention at private higher education institutions in Malaysia. This quantitative research aims to examine how human resource management practices affect employee retention, and this research will be conducted on individual employees at private higher education institutions in Malaysia, where questionnaires were distributed electronically and in hard copies to respondents. In this study, the primary sources of data collection were observed, and there was minimal interference in the process. This study was a cross-sectional time horizon since survey data are only gathered once at a certain period from respondents from various backgrounds. The target population was 1,000 people from private higher education. 98 responses were received, and all were coded and analyzed with IBM Statistical Package Social Sciences (SPSS) version 29 and Smart Pls. The study proves that rewards and recognition positively influence employee retention at private higher education institutions in Malaysia. The study suggested that employees given opportunities for training and development are more likely to stay with their organization. On the other hand, the study suggests that performance appraisal does not necessarily positively influence employee retention at Private Higher Education Institutions in Malaysia.